Implementação da política de creches nos municípios brasileiros após 1988: avanços e desafios nas relações intergovernamentais e intersetoriais - Cruz, Maria do Carmo Meirelles Toledo (2017)
This study analyzes intergovernmental and intersectoral relations in the implementation of daycare centers and the Brasil Carinhoso (BC) program, with a focus on cooperation between the Federal government and municipalities, from the municipal perspective. It seeks to understand how this policy is implemented locally and what the federal government (and on a lesser scale, the state government) has done to support municipalities in policies aimed at this educational segment. It recognizes the importance of actions of the Federal government through their regulatory and equalization functions that seek to ensure a certain uniformity and parameters in the implementation of public policies. It also shows that there is cooperation between the federal government and municipalities through programs and other forms of technical support, especially since the first decade of this century. The study starts with an analysis of Federal regulations between 1988 and 2015 and their influence on enrollment (2001-2015) and variations between States. It acknowledges that the expansion of access to daycare and municipal participation in federal programs occurred gradually and unevenly between municipalities. The study shows that the Fund for the Maintenance and Development of Basic Education and Enhancement of Education Professionals and the Brasil Carinhoso (BC) program, an initiative of the Brazil Without Misery plan both had an impact on enrollment and had mechanisms to influence municipal actions. BC was chosen because of the extensive participation in this initiative in the educational field (97% of Brazilian municipalities in 2015), because of impact it had on access to daycare for children from low-income families and because it was conceived as an intersectoral intervention. To complement this analysis, multiple case studies were carried out in 6 municipalities in two Brazilian states to identify the different ways day care policy and BC were implemented in Farias Brito, Horizonte, and Sobral in the State of Ceara, and Tarumã, Votuporanga and Osasco in the State of São Paulo). The study reveals different interpretations regarding the implementation of the right to daycare and about technical and financial cooperation between states, as well as differences in the implementation in municipalities. The Legacy of educational policy and child services in the two states explain part of these differences. The Federal government has expanded its coordination and cooperation with municipal governments, through a range of strategies, but decision-making authority has remained with the federal government, while implementation is by the municipalities, with restricted and at times informal spaces for negotiation. Contrary to expectations, states turned out to have an important role in intergovernmental cooperation, but very few states have played this role. The research suggests that, despite advances in access to daycare, there is a need to improve intersectoral coordination and BC has not led to effective intersectoral action at the local level. The challenge remains of meeting the goal established by the PNE of meeting 50% of children in daycare by 2024, and reducing inequality of access.